Analysis of clinical status of contralateral ear in cases of unilateral squamosal chronic otitis media - Ghate, Girija; Khan, Raphella; Mukhtar, Sabreena (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Squamosal COM is a condition caused by various etiological factors which are likely to affect the other side too. If diagnosed and intervened in time, the progression of the disease from simple negative middle ear pressure to cholesteatoma formation can be prevented and ear can be protected from hearing loss. Therefore it is important to assess and evaluate the contralateral ear appropriately. Methods: This prospective study included patients above six years of age suffering from unilateral squamosal chronic otitis media. Their contralateral ears were examined and assessed for any ear disease. Results: We found various conditions in contralateral ears ranging from normal tympanic membrane to various types and grades of retractions of pars tensa as well as pars flaccida and some infectious conditions too. The commonest finding was secretory otitis media (23%) and the least common was otomycosis (3%). Conclusions: Most common status in contralateral ear was found to be secretory otitis media in adult and paediatric age groups (23%). In our study, 84% of the patients showed pathology in the contralateral ear and 16% were normal, so the study proves that in patients with unilateral squamosal otitis media, with no complaints or previous history of discharge in contralateral ear shows pathology to quite a good extent¸ so the contralateral ear should always be evaluated comprehensively to efficiently diagnose any alterations and provide timely therapeutic intervention to prevent further progression of the disease and hearing loss.